Acanthopanax senticosus Promotes Survival of Tilapia Infected With Streptococcus iniae by Regulating the PI3K/AKT and Fatty Acid Metabolism Signaling Pathway - Li, Hong Xia; Qiang, Jun; Song, Chang You; Xu, Pao (Frontiers in Physiology, 2021)
Streptococcus has greatly restricted the development of healthy tilapia aquaculture. As a green and efficient feed addition, Acanthopanax senticosus (APS) has been increasingly used in culture, but it is unclear whether it represents a disease-resistant feed. Genetically improved farmed tilapia (GIFT, Oreochromis niloticus) were fed feed supplemented with 0 (control), 0.5 ‰, 1 ‰, 2 ‰, 4 ‰, and 8 ‰ APS for 56 d, after which fish were injected with 5.9 × 106 CFU/mL Streptococcus iniae into the abdominal cavity. At 96 h after infection, the cumulative survival of GIFT in control and 0.5 ‰ APS treatments was significantly lower than in other treatments; at APS supplementation rates of 1 ‰ and 2 ‰, serum glucose, triglycerides and cholesterol contents were all significantly lower than in control treatment fish. Hepatic glycogen and triglyceride contents of 1‰ APS treatment fish were significantly higher than those of control treatment fish. Transcription levels of PPAR-α, FAS, and LPL genes were up-regulated, and the expression levels of 1 ‰, 2 ‰, and 4 ‰ treatment fish were significantly higher than those of control treatment fish 96 h after S. iniae infection. After 96 h of infection, the red blood cells, hemoglobin, hematocrit, and white blood cells of fish in the 1 ‰ APS treatment were significantly lower than those of fish in 4 ‰ and 8 ‰ treatments; hepatic catalase activity was activated at 48 h, superoxide dismutase activity was also significantly up-regulated at 96 h, and the malondialdehyde content significantly decreased. The 0.5 ‰–2 ‰ APS treatments significantly activated expression of PI3K and AKT in the liver, while inhibiting expression of Caspase-9. Therefore, feed with 1 ‰ APS can promote hepatic glycogen and lipid metabolism in GIFT after infection with S. iniae, which is beneficial to alleviating oxidative stress damage and cell apoptosis in liver tissue.